'Acute flare-ups' in patients with, or at high risk of, knee osteoarthritis: a daily diary study with case-crossover analysis. Issue 8 (August 2019) - Parry, E.; Ogollah, R.; Peat, G.
Summary: Objective: To determine the natural history of flare-ups in knee osteoarthritis and their relation to physical exposures. Design: Adults aged ≥45 years with a recent primary care consultation for knee OA/arthralgia completed a daily pen-and-paper diary for up to three months, including questions on average knee pain intensity, pain descriptors, other symptoms, activity interference, and selected physical exposures (prolonged kneeling, squatting, climbing stairs, ladders, and moving/lifting heavy objects). Informed by a systematic review, flare-ups were defined a priori. We calculated the rate of flare-ups in the sample, described their nature and duration, and estimated their association with physical exposures in the prior 48 h. Results: 67 participants completed at least one month of diaries, 37 (55%) were female, mean age 62 years (SD 10.6) with a mean body mass index of 24.6 kg/m 2 (SD 5.1). 30 participants experienced a total of 54 flare-ups (incidence density 1.12 (95%CI 0.80, 1.57) flare-ups/person-days). The median duration of flare-ups was eight days (range: 2–30). During a flare-up participants were more likely to report sharp, throbbing, stabbing, burning pain, swelling, limping, stiffness, being woken by pain, taking more analgesia, and stopping usual activities. Exposure to one or more physical exposure increased the risk of a flare-up in the subsequent 48 h (odds ratio 2.19 (95%CI: 1.22, 4.05)). Conclusions: Our study with intensive longitudinal data collection suggests acute flare-ups may be experienced by a substantial number of patients. These episodes often last a week or longer, are disruptive, prompt changes in self-management, and may be triggered by high-loading physical activities.